Increased fat mass is associated with increased bone size but reduced volumetric density in pre pubertal children. - Cole, Z; Harvey, N; Kim, M; Ntani, G; Robinson, S; Inskip, H; Godfrey, K; Cooper, C; Dennison, E; Southampton Women's Survey Study Group (2012)
Recent studies have shown that obesity is associated with an increased risk of fracture in both adults and children. It has been suggested that, despite greater bone size, obese individuals may have reduced true volumetric density; however this is difficult to assess using two dimensional techniques such as DXA. We evaluated the relationship between fat mass, and bone size and density, in a population cohort of children in whom DXA and pQCT measurements had been acquired. We recruited 530 children at 6 years old from the Southampton Women's Survey. The children underwent measurement of bone mass at the whole body, lumbar spine and hip, together with body composition, by DXA (Hologic Discovery, Hologic Inc., Bedford, MA, USA). In addition 132 of these children underwent pQCT measurements at the tibia (Stratec XCT2000, Stratec Biomedical Systems, Birkenfeld, Germany). Significant positive associations were observed between total fat mass and both bone area (BA) and bone mineral content (BMC) at the whole body minus head, lumbar spine and hip sites (all p<0.0001). When true volumetric density was assessed using pQCT data from the tibia, fat mass (adjusted for lean mass) was negatively associated with both trabecular and cortical density (β=-14.6 mg/mm(3) per sd, p=0.003; β=-7.7 mg/mm(3) per sd, p=0.02 respectively). These results suggest that fat mass is negatively associated with volumetric bone density at 6 years old, independent of lean mass, despite positive associations with bone size.